Somatic embryo production and GFP genetic transformation in elite Ugandan cassava genotypes - Stephen Magambo; Alice Nabatanzi; Titus Alicai; Enoch Wembabazi; Ketra Oketcho; Immaculate Nakalembe; Henry Wagaba (Scientific African, 2024)
Friable embryogenic callus (FEC) production is a prerequisite for the genetic transformation of cassava (Manihot esculenta Crantz). This process necessitates the development of organized embryogenic structures (OES) as a precursor. However, the production of OES and FECs in cassava is dependent on the genotype. This study aimed to optimize somatic embryo production in elite Ugandan cassava genotypes (NASE13, NASE19, and NAROCASS1) and demonstrate genetic transformation using the enhanced green fluorescent protein (eGFP) gene. OES were induced by initiating leaf-lobe explants on Murashige and Skoog (MS) media at various concentrations of 24D and picloram followed by friable embryogenic callus (FEC) production and regeneration. There were highly significant differences among the different media compositions in the percentage response to OES formation (p < 0.001). NASE 13 exhibited the highest regeneration frequency of 38.4%; while NAROCASS1 had the lowest regeneration frequency of 10.5% recorded. The presence of GFP gene in NAROCASS1 was confirmed by polymerase chain reaction (PCR) analysis of the transformed lines. Compared to existing studies, this research pioneers genotype-specific optimization for somatic embryo production and successful genetic transformation in Ugandan cassava variaties. The utilization of these genotypes, already embraced by farmers, presents promising opportunities to enhance them with desirable traits, further augmenting cassava cultivation.